2008
DOI: 10.1136/ard.2007.071464
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up results after autologous haematopoietic stem cell transplantation for severe systemic sclerosis

Abstract: This study confirms that autologous HSCT in selected patients with severe diffuse cutaneous SSc results in sustained improvement of skin thickening and stabilisation of organ function up to 7 years after transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
85
1
14

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(104 citation statements)
references
References 39 publications
4
85
1
14
Order By: Relevance
“…The transplant procedure and followup were performed as previously described. 28 Written informed consent was obtained and each protocol was approved by the local ethics committee of the St Louis Hospital institute. Table 1 provides an overview of the patients' clinical characteristics.…”
Section: Patients and Methods Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transplant procedure and followup were performed as previously described. 28 Written informed consent was obtained and each protocol was approved by the local ethics committee of the St Louis Hospital institute. Table 1 provides an overview of the patients' clinical characteristics.…”
Section: Patients and Methods Patientsmentioning
confidence: 99%
“…27,28 After aHSCT, the clinical regression of skin fibrosis has been correlated with reappearance of functional B cells, thymic and extrathymic T-cell development, reconstitution of effector cells and efficient antigen presentation to reconstitute the pretransplantation immune repertoire. 29,30 However, further analysis of the immune reconstitution of the various Treg subsets and their function after aHSCT in SSc patients is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…7,8,12 The decrease in IL-2 and IL-8 levels, slight but significant decrease in TGF-β levels at M6, along with fall in mRSS may reflect downregulation of SSc fibroblast activation with a lower inflammatory status after aHSCT in dcSSc patients. Nonetheless, we show that repeated measures of TGF-β serum levels did not reflect the skin score regression post transplant.…”
mentioning
confidence: 99%
“…The aHSCT procedure at Saint-Louis Hospital (Paris, France; n = 8 patients) and LUMC Hospital (Netherlands; n = 12 patients), and follow-up were performed as described. 12 Skin fibrosis was measured by the modified Rodnan skin score (mRSS) and a decline in mRSS after aHSCT considered significant if over 25% from baseline values before transplant. 12 Control sera were collected from 18 healthy donors of the same age range as SSc patients, recruited by the Etablissement Français du Sang after informed consent.…”
mentioning
confidence: 99%
“…64 Vonk et al reported on the results of 26 patients with systemic sclerosis, 5 of whom were children, who received autologous HSCT; it is noted that 3 of the 5 children were in CR at 13-67 months post transplant, with either cyclophosphamide alone or Cyclophosphamide/ALG conditioning, and there was no TRM among the children of the cohort. 65 Finally, a study of 36 patients with refractory cytopenias (27 autologous transplants and 9 allogeneic transplants) included at least one child less than 21 years in each group. Although their outcomes are not reported independently, at 48 months post transplant, there were 9 PRs or CRs in the autologous group; 6 had transient responses, and there were 4 patients with TRM.…”
Section: Experience To Datementioning
confidence: 99%